KEDUDUKAN BAHASA JAWA RAGAM KRAMAPADA KALANGAN GENERASI MUDA:STUDI KASUS DI DESA RANDEGANKECAMATAN DAWARBLANDONG, MOJOKERTODAN DI DUSUN TUTUL KECAMATAN AMBULU, JEMBER - Khazanah, Dewianti (Jurnal Pengembangan Pendidikan, 2012)
Abstract. Javanese language is highly praised for its cultural values deeplyrooted in the structure and communicative usage of the language itself. Thevariation of krama in Javanese language reflects the wisdom of its society tohonor and respect other people in a communication. Unfortunately, the languageshift phenomenon seems unavoidable along with the major development in theglobal world. This research conveys the position of Javanese language among theyoungstersâ communication choices. This is a case study conducted in two areasnamely Desa Randegan and Dusun Tutul. The research shows that the use of Kramahas significantly shifted to Bahasa Indonesia due to childrenâs billinguality,the advance in media and technology, and inability of the learning process atschools to accommodate the communicative use of bahasa Jawa.Â Keywords: krama, language shift.